Altitudinal zonationed moss as bioindicators for pollution - Baharuddin, Zainul Mukrim; Zuhairi, Ainna Hanis; Othman, Rashidi (2015)
Placed as the crown of the mountain, Moist forest or tropical montane cloud forest (TMOF) are one of Earth’s most imperiled and neglected ecosystems. More than half of these forests are situated within Southeast Asia; those located in Malaysia are considered well studied in the region compared to others. Malaysia is known for its numerous mountains that are exceptionally rich in biodiversity and locally endemic species, but they are also threatened by human expanding actvity such are, forestry, agriculture,infrastructure, and global warming. By critically assesings the current state of moist forests—focusing on their biological fingerprints and potentials for a long-term survival—and propose conservation strategies for agricultural, forestry, tourism, and policy sectors of the Biota content as well as the effect that human interference has on it using indigenous moss species as Bio indicators through Bio monitoring, to help conserve these endangered ecosystems. There is no wrong in hoping that decision makers around the region can use the review to evaluate and improve their national strategies related to cloud forest conservation.